2017
DOI: 10.1080/21645515.2017.1349046
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Self-assembling anticaries mucosal vaccine containing ferritin cage nanostructure and glucan-binding region ofS. mutansglucosyltransferase effectively prevents caries formation in rodents

Abstract: Anticaries protein vaccines that induce a mucosal immune response are not effective. Therefore, development of effective and convenient anticaries vaccines is a priority of dental research. Here we generated self-assembling nanoparticles by linking the glucan-binding region of Streptococcus mutans glucosyltransferase (GLU) to the N-terminal domain of ferritin to determine whether these novel nanoparticles enhanced the immunogenicity of an anticaries protein vaccine against GLU in rodents. We constructed the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Rodent studies have demonstrated that vaccines containing the Gtf or GbpB protein result in detectable levels of specific salivary IgA and serum IgG. Importantly, this immunization results in significantly less total caries [244246]. It is believed that IgA and IgG present in saliva bind to Gtf or GbpB, thereby preventing bacterial adhesion to extracellular bacterial polysaccharides in dental plaque and leading to agglutination and clearance of the S. mutans organisms [246].…”
Section: Perspectives For Use Of Glycans or Glycan-binding Molecules mentioning
confidence: 99%
“…Rodent studies have demonstrated that vaccines containing the Gtf or GbpB protein result in detectable levels of specific salivary IgA and serum IgG. Importantly, this immunization results in significantly less total caries [244246]. It is believed that IgA and IgG present in saliva bind to Gtf or GbpB, thereby preventing bacterial adhesion to extracellular bacterial polysaccharides in dental plaque and leading to agglutination and clearance of the S. mutans organisms [246].…”
Section: Perspectives For Use Of Glycans or Glycan-binding Molecules mentioning
confidence: 99%
“…On week 0, seven groups of six animals each were immunized via buccal mucosa injection with 50 g of PAc, PAc plus 32 g of chitosan, PAc plus 15 g of MPL, PAc plus 25 g of Pam 3 CSK 4 , PAc-chitosan-Pam 3 CSK 4 , PAc-chitosan-MPL, or PBS and boosted on week 2. Cariogenic bacterial levels were tested from weeks 1 to 5 (35). We used swabs presoaked in PBS to collect S. mutans on fissures and smooth surfaces of molar teeth and transferred the samples to 500 l of PBS by vortexing.…”
Section: Methodsmentioning
confidence: 99%
“…mutans colonization reduced. Perhaps, with new technology such as nano delivery systems and increasing knowledge, these vaccines can be improved further and taken into human clinical trials (Li et al ; Cao et al ).…”
Section: Lessons Learned and Where Are We Today?mentioning
confidence: 99%
“…Research has also been conducted to improve the efficacy and the delivery of caries vaccines using nanotechnology. Cao et al () successfully generated self‐assembling nanoparticles by linking the GB region of glucosyltransferase (GLU) to the N‐terminal domain of ferritin (GLU‐FTH) which significantly increased the level of GLU‐specific antibodies and produced lower caries scores compared to GLU in mice. Similar results were found by Li et al () using trimethyl chitosan nanoparticles.…”
Section: Recombinant and Dna Vaccinesmentioning
confidence: 99%